RESISTENSI MASYARAKAT PESISIR PANTAI MERPATI ATAS KEBIJAKAN PEMBANGUNAN WATERFRONT CITY BULUKUMBA - Amsal, Bahrul; Jusnawati, Jusnawati (Universitas Negeri Makassar, 2024)
This study aims to determine the pattern and stage of resistance of the Merpati Bulukumba coastal community after the enactment of Regional Regulation No. 21 of 2012 concerning the 2012-2032 Bulukumba Regency Spatial Planning regarding the development of coastal areas through the Waterfront City grand design. This study used a descriptive qualitative method in the form of written narratives from the research subjects and observed behavior. In this study, the researchers determined the research location to be the coastal area of Merpati Beach in the Terang-Terang sub-district, Bulukumba district, South Sulawesi. The results showed that first, there was resistance in the coastal communities of Merpati Beach, with open patterns and strategies of resistance through rejection, demonstrations, and campaigns. Second, the process of resistance from the Pesisir Pantai Merpati community went through three stages so that they were able to influence local government policies through relocation decisions in the form of making shelter for the eviction victims.